Antibiotic Susceptibility Patterns of Uropathogens Isolated From Catheterized Patients in Al-Imam Hussein Medical City in Holy Karbala - Zahra M. Al-Hakak (Journal of Global Pharma Technology, 2018)
Objective: Indwelling urinary catheters (IUCs) are commonly used in hospitalized patients. Catheter-associated urinary tract infections (CAUTIs) are a major source of nosocomial infections in the worldwide. The present study was conducted to the etiological Bacterial pathogens of the UTI and to determine the antibiotic sensitivity pattern of pathogens isolated.  Methods: This study was carried out in AL- Imam Hussein Medical in holly Karbala city from (1st March, 2017) to (30st June, 2017).Total (300) urine samples were tested bacteriologically and for antibiotic susceptibility using standard procedures. Results: A total (300) patients,(111) by(37%) were female and (189) by (63%) were male with indwelling urinary catheters were studied divided into four groups according to hospital ward. The highest percentage of age group was seen in (36-45) years group. Uropathogens were isolated from (244) patients sample only. The bacterial isolates included E. coli (53), Pseudomonas aeruginosa (99), Klebseillapneumonia  (22), Staphylococcus aureus (20), Coagulase negative Staphylococcus (16), Candida albicans (14), Enterococcus faecalis (8), B hemolytic  Streptococci (6) and Serratiamarcesens (6). All isolated bacteria display variation in sensitivity and resistance pattern. Conclusions: This study observed that Pseudomonas aeruginosais the main organism which isolated from Catheterized patients caused UTI. In addition, the study showed that E. coli isolates were the predominant pathogens and showed increasing resistance pattern to the commonly drugs which used in present study.Keywords: Urinary Catheter, Urinary Tract, Infection, Antibiotic, Patterns, Holy Karbala.